2002
DOI: 10.1038/sj.gt.3301608
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental equine osteoarthritis by in vivo delivery of the equine interleukin-1 receptor antagonist gene

Abstract: Osteoarthritis in horses and in humans is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
344
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(377 citation statements)
references
References 31 publications
4
344
1
9
Order By: Relevance
“…Additional studies in established experimental models (7,8) will be required in order to evaluate the effects of SOX9 overexpression in OA cartilage in vivo. The present findings provide motivation to further develop this therapeutic gene-transfer approach to the treatment of OA in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies in established experimental models (7,8) will be required in order to evaluate the effects of SOX9 overexpression in OA cartilage in vivo. The present findings provide motivation to further develop this therapeutic gene-transfer approach to the treatment of OA in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Application of therapeutic genes to OA cartilage may offer potent alternatives for reestab- Most of the current approaches to restoring the physiologic balance in injured articular cartilage are based on the delivery of factors that modulate the metabolic functions of chondrocytes, such as agents that counteract the processes of matrix degradation or ones that enhance the synthesis of matrix components. Protective effects of an IL-1 receptor antagonist (IL-1Ra) sequence against IL-1-induced cartilage breakdown have been documented in experimental models ex vivo (5,6) and in vivo (7,8). The transfer of the gene for a heat-shock protein (Hsp70) was also shown to afford protection against cellular injuries in chondrocytes (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mi et al 34 found that delivery of Ad.IGF-1 to the knees of normal rabbits and those with experimental arthritis was capable of stimulating an increase in proteoglycan synthesis in articular cartilage without adverse effects. Frisbie et al 35 found that delivery of an adenovirus encoding the equine homolog of IL-1Ra into the joints of horses with experimental OA resulted in significant clinical improvement in both pain and disease activity, and preservation of articular cartilage.…”
Section: Gene Transfer To Cells In the Synovial Liningmentioning
confidence: 99%
“…Anti-TNFα, PEGylated soluble TNFα (Fox & Stephens, 2010); (Frisbie et al, 2002); (Evans et al, 2004); (Meijer et al, 2003) (Zafarullah et al, 2003); (Martel-Pelletier, 1999); (Furman et al, 2006); (Fukui et al, 2001); (Evans et al, 2004); (Elsaid et al, 2009) Matrix protection…”
Section: Irap/ Il-1ramentioning
confidence: 99%